2021
DOI: 10.3389/fcvm.2020.599334
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis and Coagulopathy in COVID-19: Current Understanding and Implications for Antithrombotic Treatment in Patients Treated With Percutaneous Coronary Intervention

Abstract: Coronavirus disease 2019 (COVID-19), a respiratory syndrome, is a global pandemic. Therefore, there is an urgent need to explore mechanisms implicated in the pathogenesis of the disease. Clinical and autopsy studies show a complex chain of events preceding COVID-19-related death. The disease is characterized by endothelial dysfunction, platelet activation, thrombosis, coagulopathy, and multiple organ failure. Globally, millions of patients with coronary heart disease undergo percutaneous coronary intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 105 publications
0
21
0
3
Order By: Relevance
“…In some cases, this immune response is dysregulated and leads to cytokine storm. These events occur concurrently with endothelial dysfunction and platelet activation which in turn result in increased vascular permeability, widespread inflammation, hypercoagulation, multiple organ damage, and failure [ 26 , 27 ]. In severe cases, this cascade of events causes enough cellular damage releasing multiple intracellular contents into blood circulation, including nucleotides, which are subsequently metabolized into UA, and eventually increase serum UA level.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, this immune response is dysregulated and leads to cytokine storm. These events occur concurrently with endothelial dysfunction and platelet activation which in turn result in increased vascular permeability, widespread inflammation, hypercoagulation, multiple organ damage, and failure [ 26 , 27 ]. In severe cases, this cascade of events causes enough cellular damage releasing multiple intracellular contents into blood circulation, including nucleotides, which are subsequently metabolized into UA, and eventually increase serum UA level.…”
Section: Discussionmentioning
confidence: 99%
“…It also appears that COVID-19 infection can promote cardiovascular disorders. The virus enters host cells through the binding of the spike protein to Angiotensin converting enzyme 2 (ACE-2) on pulmonary epithelial cells causing damage to the lungs as well as directly binding to vascular endothelial cells of other organs, such as the kidneys and heart [9,10]. It is possible that, due to the mediating effects of ACE-2 on blood pressure, those with hypertension could have some dysregulation of ACE-2 function therefore predisposing individuals to severe conditions and mortality [11].…”
Section: Cardiovascular Functionmentioning
confidence: 99%
“…It is possible that, due to the mediating effects of ACE-2 on blood pressure, those with hypertension could have some dysregulation of ACE-2 function therefore predisposing individuals to severe conditions and mortality [11]. It has also been suggested that the occurrence of cardiovascular events in those with COVID-19 is caused by inflammation and vascular remodelling brought about by endothelial dysfunction [9,12]. Such dysfunction is due to 'cytokine and coagulation storms' that can compromise the integrity and physiological anti-thrombotic and anti-inflammatory properties of the endothelium within vessels [13].…”
Section: Cardiovascular Functionmentioning
confidence: 99%
“…According to guidelines recommendations, anticoagulant drugs, especially low molecular weight heparins (LMWH), in prophylactic or even therapeutic doses, should be started as soon as possible after confirming the SARS-CoV-2 infection to prevent the occurrence of life-threatening complication [6][7][8]. Nevertheless, data over hemostasis disturbances related to COVID-19 are scarce in the medical literature [3,[9][10][11]. Except for the severe examples of disseminated intravascular coagulopathy observed in severe cases hospitalized in the intensive care units, further hemorrhages with diverse locations have been reported [1][2][3].…”
Section: Case Presentationmentioning
confidence: 99%
“…Except for the severe examples of disseminated intravascular coagulopathy observed in severe cases hospitalized in the intensive care units, further hemorrhages with diverse locations have been reported [1][2][3]. In the same vein, spontaneous hematomas developed in patients suffering or recovering from COVID-19 were rarely described [7,14], being mostly associated with the treatment with LMWH [1,9,11]. According to the guidelines, LMWH are the treatment of choice for patients with deep vein thrombosis (DVT), and are also used as prophylaxis in COVID-19 [15][16][17].…”
Section: Case Presentationmentioning
confidence: 99%